Outcomes of ALK positive lung cancer patients treated with crizotinib or second-generation ALK inhibitor: a monoinstitutional experience - De Carlo, Elisa (Oncotarget, 2018)
Rearrangement in the anaplastic lymphoma kinase (ALK) gene is one of the oncogenic drivers in non-small cell lung cancer (NSCLC) patients. Several ALK inhibitors (ALKis) have been developed and have demonstrated their efficacy, however the best treatment strategy for ALK positive NSCLC patients has yet to be determined. Our retrospective study has investigated the outcome of 40 ALK-rearranged NSCLC patients treated with two different sequential strategies in our Institute; a “classical group”, treated with crizotinib followed by second or third generation ALKis, and the “experimental group”, treated upfront with a second generation ALK inhibitor. The primary endpoints investigated were Progression-free survival (PFS) and intracranial activity. The analysis has revealed a significant improvement in PFS (p = 0.050) in the experimental group, furthermore none of these patients developed brain metastasis. There was no statistically significant difference in OS, but all patients in the experimental group were still alive after a median follow up of 15 months. Our retrospective analysis suggests that systemic and intracranial efficacy tends to be better in the experimental group; randomized prospective studies could confirm our observations.